Elaboration of Maqashid Sharia Values in Forming Transformational Leadership - Arifin, Samsul; Awaludin, Azrul Afrillana; Yusril, Yusril (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2024)
This study delves into the intricate interplay between transformational leadership and the Maqashid Shariah framework within the context of organizational triumph, drawing from established theory and a comprehensive analysis of prior research through literature review. Transformational leadership emphasizes visionary outlooks, motivational dynamics, and constructive influence, while Maqashid Shariah underscores Islamic ideals of prosperity. The amalgamation of these paradigms holds promise for cultivating leadership that is not solely effective in material terms but also morally grounded and adaptable amidst global transformations. Within the Maqashid Shariah framework, leaders are tasked with upholding religious tenets, safeguarding life, property, lineage, and rationality in their decision-making and actions, fostering inclusivity in the workplace, promoting mental well-being, ensuring economic equity, nurturing a morally upright future generation, and fostering intellectual growth. Consequently, leaders imbued with the ethos of Maqashid Shariah serve as catalysts for positive change, propelling organizational objectives forward with Islamic ethics as their moral compass.